Effect of Different Wheat Sprouting Conditions on the Characteristics of Whole-Wheat Flour - Navarro, José Luis (2024)
Fil: Navarro, José Luis. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas; Argentina.